(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
When teaching English to speakers of other languages, especially ESL (English as a Second Language) students, phonetic training is essential. Proficiency in phonetics can greatly improve students’ listening comprehension, pronunciation, and general communicative competence. This article highlights the value of phonetic education, looks at the difficulties teachers have, and offers solutions for its application in ESL classes.